Effects of neuromuscular training on stability in volleyball athletes: a systematic review and meta-analysis - Yang, F.; Lu, C.; Yun, X.; Qian, C. (Frontiers in Sports and Active Living, 2025)
Introduction: Neuromuscular training (NMT) has been recognized as an effective strategy for improving sensorimotor function and mitigating injury risk in athletic populations. This systematic review and meta-analysis evaluated the effects of NMT on dynamic and static stability in volleyball players. This review assessed potential moderators, including sex and body region. Methods: Relevant randomized controlled trials published between 1 January 2015, and 30 June 2025, were identified through systematic searches of major electronic databases. The search was limited to English-language publications and was conducted across Web of Science, PubMed, the Cochrane Library, Scopus, ScienceDirect, and PEDro. Following the screening and eligibility assessment, seven studies met the inclusion criteria and were included in the final analysis. Results: Random-effects meta-analysis indicated that NMT was associated with moderate improvements in overall stability [SMD = 0.63, 95% CI (0.35, 0.9), I2 = 67.5%]. Moderator analyses suggested that benefits were more apparent in the upper limb compared to the lower limb and showed sex specific adaptations: males exhibited greater improvements in upper limb stability, whereas females showed more pronounced effects in the lower limb. Discussion: Potential optimization mechanisms include enhanced lower-limb biomechanical responses through plyometric training, improved upper-limb kinetic chain synergy, and increased proprioception. NMT induced gender differentiated patterns of stability improvement in volleyball athletes, with males benefiting more from upper-body training while female athletes demonstrated greater adaptability in enhancing lower-body stability.